2011
DOI: 10.1111/j.1365-3091.2011.01240.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and magnesium‐limited dolomite precipitation at Deep Springs Lake, California

Abstract: Dolomite [Ca,Mg(CO3)2] precipitation from supersaturated ionic solutions at Earth surface temperatures is considered kinetically inhibited because of the difficulties experienced in experimentally reproducing such a process. Nevertheless, recent dolomite is observed to form in hypersaline and alkaline environments. Such recent dolomite precipitation is commonly attributed to microbial mediation because dolomite has been demonstrated to form in vitro in microbial cultures. The mechanism of microbially mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 71 publications
(169 reference statements)
7
79
0
1
Order By: Relevance
“…Precipitation of primary dolomite in the Coorong was later associated with BSR (Wright & Wacey, ; Wacey et al ., ), while Meister et al . () suggest that dolomite precipitation in Deep Springs Lake and Coorong is an abiotic process. Zhang et al .…”
Section: Discussionmentioning
confidence: 97%
“…Precipitation of primary dolomite in the Coorong was later associated with BSR (Wright & Wacey, ; Wacey et al ., ), while Meister et al . () suggest that dolomite precipitation in Deep Springs Lake and Coorong is an abiotic process. Zhang et al .…”
Section: Discussionmentioning
confidence: 97%
“…A fundamental structural barrier stemming from the lattice limitation on the spatial configuration of CO 3 groups in magnesite crystals, and cation hydration effect that constrains dolomite formation were observed by Xu et al [53]. Ca and Mg are found to be the limiting factor for the dolomite precipitation in a saline lake in California [15].…”
Section: Dolomite Enigma In Sedimentary Geologymentioning
confidence: 90%
“…In fact, mineral precipitation is not only a chemical process, it also involves with biochemical reactions, such as the methanogenic decomposition of organics into CO 2 and CH 4 , which gives rise to partial pressure of CO 2 and concentration of CO 3 2− in aqueous solution. Latest evidence shows that metals tend to adsorb onto carboxyl surface and then crystallize with much faster reaction rate and much less energy required to overcome obstacles in chemical potentials that may be encountered in a reaction [14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…ions made the very fine dolomite directly precipitate from the evaporating lake waters (Burn et al 2000). Secondly, Meister et al (2011) reported that fine-grained dolomite probably precipitates directly in the well-aerated water column from highly alkaline brine, whereas microbial alkalinity production and pH increases are negligible. So the precipitation of dolomites from saline lake water should be considered in light of the possible origin of very fine rim cement and dolomite lamellae within ooids in the Sikou Sag, and inferring a similar genesis for the origin of dolomite mud should also be explored in dolomitized mudstone.…”
Section: Mechanism Of Dolomite Formationmentioning
confidence: 99%
“…Very fine crystalline dolomites are widely formed in varied types of lacustrine systems (Meister et al 2011;Mauger and Compton 2011;Last et al 2012;Casado et al 2014;Meng et al 2014a, b;Köster and Gilg 2015;Lu et al 2015). They may form by replacement (dolomitization) of micrite matrix or allochems, or alternatively, they may occur as intraparticle and interparticle cements (Rosen and Coshell 1992).…”
Section: Introductionmentioning
confidence: 99%